Resistive and capacitive technology recipes for peak cooling load reductions in the global south. (15th May 2023) - Chung, Woong June; Khattak, Sanober Hassan; Cecinati, Francesca; Jeong, Su-Gwang; Kershaw, Tristan; Allen, Steve; Park, Cheol-Soo; Coley, David; Natarajan, Sukumar
Abstract: Buildings in the Global South are expected to drive a tripling of global cooling energy demand by 2050. In countries such as India, growth in energy use far outstrips growth in population, often to the ratio 3:1. While several building-level technologies exist that could help reduce peak and total demand, the technologies, or combination of technologies, that would offer the greatest peak reduction in the range of climates in the Global South is unknown as previous work has focused on mid latitudes. Hence, we use computer simulations to study, for the first time, six different cooling-driven peak-shaving technologies covering 19 different climates in the Global South. Using Latin Hypercube Sampling to account for the uncertainties arising from building variants and technology performance, we conduct a total of 266, 000 annual hourly simulations. While thermally activated building systems and phase change materials deliver the largest reductions in peak and total demand, water storage is the most consistent in reducing the peak, yet had a possible increase in annual demand. We also develop technology combinations, or "recipes", which suggest that the range of attainable peak and total demand reduction is between 19% - 95% and 20%–99% respectively, depending on the climate. Given the scale of the potential reduction, our results justify the investment in such technologies by governments and others to deliver major reductions in energy demand and peak load in the Global South, but if incorrectly designed, it is clear they may result in reduced energy security and increased carbon emissions. Highlights: First study on building technologies to reduce peak and total demand in the Global South. While thermally activated systems and phase change materials deliver the largest reductions, water storage is the most consistent in reducing the peak. Investing in such technologies could help buildings in the Global South significantly improve energy security.